Theoretical performance analysis of a new hybrid air conditioning system with two-stage energy recovery in cold winter. (September 2020) - Yang, Yang; Ren, Chengqin; Tu, Min; Luo, Baojun; Fu, Jianqin
Highlights: Proposed hybrid system incorporates a fresh air conditioner with refrigerant system. Fresh air conditioner has a heat-exchanger network for two-stage energy recovery. Four independent affecting parameters are included for parametric analysis. Optimum air-water heat capacity ratio of packed tower is found to be between 0.4–0.6. Average energy-saving rate of the proposed hybrid system is 44.0%. Abstract: Energy recovery technologies can effectively improve the energy efficiency of air-conditioning systems and significantly reduce building energy consumption. In this paper, a parametric analysis and energy-saving potential evaluation for a new hybrid air conditioning system (HAC) is carried out theoretically based on developed models. The proposed HAC incorporates into a conventional mechanical vapor compression air conditioning system with an independent fresh air conditioner which is composed of a network of heat exchangers, including a packed bed and three air-water finned coils. Under cold winter climate, in the fresh air conditioner, a packed bed is coupled with a water-air heat exchange coil to form a total energy recovery loop. A run-around sensible energy recovery loop is also integrated in the system to produce a two-stage energy recovery effect. Moreover, a sprayer is installed upstream of the two-stage energy recovery process for fresh air humidification, and a fresh air recirculation duct is equipped for frost-free operation. In the parametric analysis, four independent affecting parameters are included: the air-to-water heat capacity ratio, the indoor temperature, the ambient temperature, and the ratio of recirculation fresh air. The energy-saving potential of the HAC is also evaluated for applications in seven typical cities located in middle-lower Yangtze River region of China over the winter period (December, January and February). The results show that compared with the conventional system with electric humidification, the HAC has an average energy saving rate of 44.0%, and its average power saving per hour is 13.41 W m −2 .